Réseaux sociaux, construction de l’identité institutionnelle et nouvelles formes de visibilité - Daniela Roventa-Frumusani; Elena Farcaș (Communication)
The authors examine how Romanian government ministries use the Internet to inform the public. They analyze ministries’ websites and official Facebook pages from an interdisciplinary perspective to identify their strategies for promoting transparency, trust-based relations between institutions and the public, and public debate.